전문체육정책 의제설정과정에 영향을 미치는 요인에 대한 탐험적 분석 : 우수선수양성지원 정책을 중심으로 - 강지현; Jeehyun Kang; 손정화; Junghwa Son; 신호진; Hojin Shin; 권기성; Kisung Kwon (Ch'eyuk kwahak yŏn'gu, 2020)
[목적] 본 연구는 정책 의제 설정 과정을 설명하는 다중흐름모형을 통해 전문체육 정책 수립을 위한 첫 단계인 의제설정과정에 영향을 미치는 요인을 도출하고자 했다. [방법] 이를 위해 질적연구 접근으로 선행연구, 언론자료, 심층면담을 통해 자료를 수집하였다. 내용분석을 통해 요인을 도출하고 이를 기반으로 단계별 범주화 및 항목화를 통해 Kingdon (1984)의 다중흐름모형에 기반하여 문제, 정책, 정치의 흐름이라는 관점을 기준으로 각각의 주요요인을 도출했다. [결과] 결과를 살펴보면 한국 전문체육 정책에 영향을 주요 요인의 문제, 정책, 정치 흐름을 구성하는 관점에서 각각의 주요요인을 도출할 수 있었다. 먼저, 문제흐름의 경우 국제스포츠 대회 성적, 국제 스포츠 대회 개최 및 참가, 전문체육선수 수급, 전문체육선수 및 종목 지원 시스템, 학생 학습권/인권/학원 스포츠, 정책의 현실성, 스포츠 전문가 및 기관의 역량, 전문체육에 대한 인식이 세부요인으로 나타났다. 둘째 정책 흐름의 경우 스포츠 행정기구 개편, 전문체육선수 육성 저책, 상위 정책 및 제도개편, 전문체육선수를 위한 인센티브 및 지원제도, 종목별 특성 및 형평성에 대한 정책공동체의 가치, 예산, 국제 대회 유치 정책이 세부 요인으로 도출되었다. 마지막으로 정치의 흐름을 구성하는 세부 요인은 국민 통합/국위선양/남북화해 협력을 위한 전문체육, 정권변화에 따른 스포츠 행정기구 개편, 정권 변화에 따른 전문체육 상위정책 변동으로 나타났다. [결론] 한국 전문체육 정책에 대한 해당 연구 결과와 추후의 적극적인 연구활동이 전문체육 본질에 대한 사회적 합의와 공감대 형성에 기여하여 궁극적으로 전문체육 기저 문화의 핵심요소로 공고화되는데 도움이 될 수 있을 것으로 사료된다. [Purpose] This research aims to find out factors affecting policy at the agenda setting phrase. In order to analyze, Multiple Streams Framework(MSF) was adopted. Based on the frame, policy problem stream, policy alternative stream, political stream, window of policy change, and policy entrepreneur were applied for analytical framework. [Methods] The research conducted qualitative research with triangulation. Data were collected by in-depth interview and literature review including newspaper and previous researches. Content analysis was done for deriving factors. Then categorization and itemization were conducted. [Results] For the result, factors derived from the study were not different from factions mentioning at MSF. For policy problem stream perspective, this study draw International Sports Event Result, Hosting International Sports Event, Elite Sports Athletic Recruiting, Athletic and Sports Category Supporting System, Student Study Right/Student Human Right/Sports Academy, Policy Reality, Sport Expert/Institute Capability, Perception of Elite Sport Origin. factors. In the case of Policy Alternative Stream, This study finds Sports Related Administrative Organization Restructure, Supporting Policy of Elite Athletic Promoting Restructure, Parent Policy of Elite Athletic Promoting Policy, Parent Institution of Elite Athletic Promoting Law, Incentive Institution for Elite Athletic, Supporting Institution for Elite Athletic, Value of Policy Community for Sports Category Feature, Value of Policy Community for Sports Category Fairness, Budget, International Sports Event Hosting Policy factors. Lastly, in the political perspective, this study figures out Elite Sports for Nation Integration, Elite Sports for Enhancing National Prestige (North and South Replacement), Elite Sports for Inter Korean Reconciliation and Cooperation, Sports Related Administrative Organization Restructure Following Regime Change, Parent Policy Change of Elite Sports Following Regime Change factors. [Conclusions] The research has academic implication for generating elite sport policy agenda setting model as well as practical implication for urging effective participation of various practitioners concerning elite sport.